2022
DOI: 10.1029/2022jd037177
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire Smoke Influence on Cloud Water Chemical Composition at Whiteface Mountain, New York

Abstract: Simulations using the Weather Research and Forecast modeling system with Chemistry (WRF-Chem-SMOKE) for northern Canada (Lu & Sokolik, 2013) and the western United States (Twohy et al., 2021) show that clouds significantly influenced by biomass burning smoke have increased cloud droplet number concentrations and decreased cloud droplet sizes. In this way, biomass burning particles can delay the onset of precipitation, affecting the lifetime, chemistry, and microphysical properties of clouds (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 172 publications
0
3
0
Order By: Relevance
“…Loría-Salazar et al (2021) analyzed smoke height boundary-layer effects using NASA MODIS and VIIRS aerosol products, using these to document the influence of mountainous terrain on vertical aerosol profiles during extreme smoke events. A study by Lee et al (2022) investigated cloud water samples over eight summers at Whiteface Mountain, New York. These authors found that nearly half of the summertime cloud water samples were influenced by wildfire smoke, which contributed to the addition of sulfate, ammonium, potassium, and total organic carbon.…”
Section: How Does Fire Work? Physical and Chemical Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…Loría-Salazar et al (2021) analyzed smoke height boundary-layer effects using NASA MODIS and VIIRS aerosol products, using these to document the influence of mountainous terrain on vertical aerosol profiles during extreme smoke events. A study by Lee et al (2022) investigated cloud water samples over eight summers at Whiteface Mountain, New York. These authors found that nearly half of the summertime cloud water samples were influenced by wildfire smoke, which contributed to the addition of sulfate, ammonium, potassium, and total organic carbon.…”
Section: How Does Fire Work? Physical and Chemical Processesmentioning
confidence: 99%
“…A study by Lee et al. (2022) investigated cloud water samples over eight summers at Whiteface Mountain, New York. These authors found that nearly half of the summertime cloud water samples were influenced by wildfire smoke, which contributed to the addition of sulfate, ammonium, potassium, and total organic carbon.…”
Section: How Does Fire Work? Physical and Chemical Processesmentioning
confidence: 99%
“…3 ) are also the major causes behind acid deposition, a process that can have detrimental ecosystem effects such as decreased aquatic biodiversity, calcium depletion from soils, release of toxic aluminum (Gorham, 1998;Likens et al, 1998;Driscoll et al, 2001;Menz and Seip, 2004) and deterioration of building materials (Xie et al, 2004;Bravo et al, 2006). These growing societal and environmental problems helped influence and shape amendments to the Clean Air Act in the 1990s focusing on the criteria air pollutants SO 2 and NO x .…”
Section: Introductionmentioning
confidence: 99%